Never let me go - Ishiguro, Kazuo, 1954- (Faber and Faber, 2006)
From the acclaimed author of The Remains of the Day and When We Were Orphans, a moving new novel that subtly reimagines our world and time in a haunting story of friendship and love. As a child, Kathy-now thirty-one years old-lived at Hailsham, a private school in the scenic English countryside where the children were sheltered from the outside world, brought up to believe that they were special and that their well-being was crucial not only for themselves but for the society they would eventually enter. Kathy had long ago put this idyllic past behind her, but when two of her Hailsham friends come back into her life, she stops resisting the pull of memory. And so, as her friendship with Ruth is rekindled, and as the feelings that long ago fueled her adolescent crush on Tommy begin to deepen into love, Kathy recalls their years at Hailsham. She describes happy scenes of boys and girls growing up together, unperturbed-even comforted-by their isolation. But she describes other scenes as well: of discord and misunderstanding that hint at a dark secret behind Hailsham's nurturing facade. With the dawning clarity of hindsight, the three friends are compelled to face the truth about their childhood-and about their lives now. A tale of deceptive simplicity, Never Let Me Go slowly reveals an extraordinary emotional depth and resonance-and takes its place among Kazuo Ishiguro's finest work.